Implementasi Pendidikan Karakter Melalui Pemanfaatan Budayasekolah di SD Negeri Kyai Mojo Yogyakarta Tahun Ajaran 2016/2017 - Angga Setya Budi; Kristi Wardani (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: The purpose of the research is to describe (1) the implementation of character education through the utilization of school culture, (2) the value developed in the implementation of character education through the utilization of school culture, (3) the obstacles experienced in the implementation of character education through the utilization of school culture. This research is a qualitative descriptive research. Place of study at Public Elementary School Kyai Mojo Yogyakarta. The time of study was conducted in the even semester of2016/2017. Data collection techniques use observation, interview and documentation. The research instruments consist of observation sheets and interviews. The data validity test is performed by increasing persistence, triangulation, and using reference materials. Data analysis techniques use data collection, data reduction, data presentation, and conclusions. The results showed (1) the implementation of character education conducted routine activities, spontaneous activities, exemplary, conditioning and teaching. (2) The values developed are the values of discipline, religion, curiosity, homeland love, reading, social care, caring, diligent, responsibility, courage, honesty, and thoroughness. (3) Obstacles are experienced that some parents are less supportive of school programs and some parents have lower middle-class economic ability so less attention to education of his child. Suggestion, add character formation program, teachers emphasize more on the planting of commendable characters, students get used to do positive behavior.